WORK ON THE DEVELOPMENT AND ENRICHMENT OF THE VOCABULARY AMONG THE ELEMENTARY SCHOOL STUDENTS DURING THE UKRAINIAN LANGUAGE LESSONS ON SYNONYMS AND ANTONYMS - Royik, O. Ju. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article brings attention to the issues of the development of conversational skills among the elementary school students in modern schools. The article defines methods, conditions and ways to enrich the vocabulary among the elementary-school age students during the lessons dedicated to learning synonyms and antonyms. The article also studies the role and significance of the development of the conversation skills and vocabulary expansion, which form the basis for further successful formation of the language and conversation culture of the person.